Changing Times: Big Screen Getting Streamed - Vikas Rajpopat (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2022)
Let’s keep first thing first. What is over the top media? “An over-the-top (OTT) media service is a media service offered directly to viewers via the Internet. OTT bypasses cable, broadcast, and satellite television platforms; the types of companies that traditionally act as controllers or distributors of such content.”1 After the arrival of internet in our lives, things changed drastically. OTT media services are changing the way we consume entertainment. Leading Indian news channel Zee News states the reasons why we are seeing boom in OTT platforms. “The main reason OTT platforms have become so popular is that viewers can directly access these platforms on the go. Since you can access these platforms from your mobile or laptop, you don’t need to find a television to watch your favorite TV show.